CODESRIA Bulletin, No. 4, 2020 - Journal System, (CODESRIA Bulletin, 2020)
In this issue Editorial, Godwin R. Murunga & Ibrahim O. Ogachi ------------ 1 1. The Randomista Rampage in Development Economics: A View from the Trenches, David Ndii ------3 2. Evidence as Cliché: Using Trials to Tamper with Governance, Seye Abimbola----------- 9 3. The Nobel Prizes, Racism, and the Economy of Prestige, Wandia Njoya ------------- 17 4. Economics Experiments in Africa: How Many and by Whom? Amma Panin ------------ 23 5. Structural Change, Inequality, and Inclusive Development: Case of Sub-Saharan Africa, Jimi Adesina -------- 29 6. ‘Mandela-wash’: How Invoking Mandela’s Name Cannot Obscure Past Injustice, Robin Cohen -------- 37